The gastronomic experience: motivation and satisfaction of the gastronomic tourist—the case of puno city (Peru) - Cordova-Buiza, Franklin (2021)
ABSTRACT Gastronomy is a fundamental aspect of culture in daily life, through which tourists can discover the cultural heritage of the places they visit. Therefore, culinary pleasure is a decisive factor in choosing a travel destination; at the same time, it is essential for shaping tourists’ satisfaction regardingtheirtravelexperience. Thisresearchseekstostudythegastronomicexperiencesofforeign tourists visiting the city of Puno (Peru) during the celebration of the festival of the Virgen de la Calendaria, recognized as an Intangible Cultural Heritage event by UNESCO. The results of this research highlighted the existence of three groups of tourists (referred to as survivors, enjoyers and experiencers) based on their perceptions of gastronomic experiences in the city. We also concluded that there are signiﬁcant differences in each of the groups in terms of their motivation for visiting the city,basedongastronomy. Finally,theresultsallowustoconcludethatthelevelsoftouristsatisfaction aredifferent,dependingontheirattitudetowardgastronomy,asclassiﬁedbythegroupingsobtained.